Cummins in China - Rosenthal, Jean W., 1945- (SAGE Knowledge. Cases., 2016)
Cummins had combined its global expertise with solutions developed in China for the China market. But the introduction of each new level of emissions standards came with regulatory uncertainty. To meet the needs of the China market, engines had to be less expensive and more fuel efficient than engines developed to meet similar standards in North America and the U.S. Even more challenging, the uncertainty around implementation of each new round of emissions standards made it difficult for Cummins to plan its manufacturing and meet its Mission Statement.